DROWNING IN WORDS? USING NUDIST TO ASSIST IN THE ANALYSIS OF LONG INTERVIEW TRANSCRIPTS FROM YOUNG INJECTING DRUG USERS - Loxley, Wendy (2001)
This paper describes the analysis, using the software package NUDIST 2.3, of interview data from a qualitative study of young drug injectors and their risk of HIV/AIDS. The aims and processes of the study are briefly described, and the method of analysis detailed. NUDIST 2.3 is a sophisticated computer software system for managing, organising and supporting qualitative data analysis. The data for this study consisted of word for word transcripts of 105 90-minute interviews: the management and organisation of this quantity of data was a formidable task in itself and this will be described, as will the development of initial coding frames (with cautionary tales) and the process by which increasing levels of analytic abstraction were generated. Reliability and validity has been held by some researchers to be irrelevant to qualitative research, but this is not the position adopted by this study. The paper ends with a discussion on reliability and validity and how such issues were addressed in the analysis.